General infection prevention, mitigation, and control procedures implemented in the university education during the COVID-19 pandemic to achieve classroom attendance: a successful community case study - Monge, Diana; Gallego-Gil, Ana; Neria, Fernando; Canellas, Soledad; Caballero, Fernando; Díaz de Bustamante, Ana; Samper, Mónica (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic entailed confinement and elimination of face-to-face university classes in Spain. The Francisco de Vitoria University in Madrid (UFV by its Spanish acronym) implemented risk management systems to enable on-campus university activity to avoid a negative impact on students, teachers, and faculties. Methods A tracking/registry system was implemented to collect data, identify COVID-19-related cases, implement containment measures, and do follow-up in the UFV community (administration/services personnel [ASP], teaching/research personnel [TRP], and students), from September 2020 to April 2022. In addition, a prevention plan was implemented on campus to avoid COVID-19 spreading. Satisfaction with these measures was assessed through an online questionnaire. Results A total of 7,165 suspected COVID-19 cases (84.7% students, 7.7% ASP, 6.5% TRP) were tracked (62.5% female cases, mean age (±SD) 24.8 years (±9.2 years)), and 45% of them confirmed (82% symptomatic/16% asymptomatic), being the student group that with the highest percentage (38.3% total tracked cases). The source of infection was identified in 50.6% of the confirmed cases (90.2% located off-campus). Nineteen COVID-19 outbreaks were registered (inside-10/outside-9). COVID-19 incidence rates were similar or lower than those reported in the Community of Madrid, except in the last wave, corresponding to Omicron variant. The degree of satisfaction (scale 1–6) with the implemented measures was high (scores 4.48–5.44). Conclusion During the COVID-19 pandemic, UFV control measures, periodic monitoring, and the effectiveness of the tracking system have contributed to maintaining classroom teaching, guaranteeing health and safety. UFV has adapted to a new reality as an example of good practice for future pandemics or emergency situations.